On the simulation technique of stochastic processes and nonlinear vibrations - Menh, Nguyen Cao; Tri, Tran Duong (Vietnam Journal of Mechanics, 1994)
In this paper the procedure and program for simulation of stochastic processes are represented. The program is applied to nonlinear mechanical systems subjected to stochastic stationary excitation. The results obtained are compared with the ones from other methods which are used for estimating the exactitude of simulation technique.